2020
DOI: 10.1080/23279095.2020.1788032
|View full text |Cite
|
Sign up to set email alerts
|

Does bilingualism influence neuropsychological test performance in older adults? A systematic review

Abstract: Objective: Using standardized tests which have been normed on monolinguals for the assessment of bilinguals presents challenges to the accurate characterization of cognitive profile as the literature provides compelling evidence for the influence of bilingualism on cognitive abilities. However, little is known about the generalizability of these findings to clinical neuropsychology. The aim of this review was to address this gap by summarizing current evidence on the performance of bilingual older adults on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…This result indicated that the level of acculturation and integration differed (with those picking German being more integrated) and that this level was associated with cognitive performance. Another systematic review on bilingualism as an influencing factor in test performance in older adults indicates that migration status, acculturation level, and language of neuropsychological testing need to be considered when assessing bilingual older adults [ 48 ]. In line with this, the systematic review on migration and cognition conducted by Xu et al (2017) [ 9 ] demonstrated a significant association between a higher level of acculturation and better performance in cognitive functioning among migrants.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that the level of acculturation and integration differed (with those picking German being more integrated) and that this level was associated with cognitive performance. Another systematic review on bilingualism as an influencing factor in test performance in older adults indicates that migration status, acculturation level, and language of neuropsychological testing need to be considered when assessing bilingual older adults [ 48 ]. In line with this, the systematic review on migration and cognition conducted by Xu et al (2017) [ 9 ] demonstrated a significant association between a higher level of acculturation and better performance in cognitive functioning among migrants.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming normative performance in examinees with LEP on nonverbal tests on rational grounds alone increases the risk of significant errors in the clinical interpretation of scores (Celik et al, 2020; Funes et al, 2016; Gasquoine & Gonzales, 2012). In fact, our results challenge the notion of “LEP profile” as a unitary construct.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research demonstrated that LEP can be a significant confound in test result interpretation even in cognitively high-functioning examinees (Ali, Brantuo, et al, 2022; Erdodi et al, 2017a). Consequently, existing norms may not apply to individuals with LEP (Celik et al, 2020; Funes et al, 2016; Gasquoine & Gonzales, 2012), as they systematically underestimate verbal skills in general – while perhaps providing an accurate measure of English proficiency. As the world grows diverse due to migration and the percentage of bilinguals increases both in Europe and the USA (Eurostat, 2018; Ryan, 2013), so do the chances of encountering patients with LEP in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also vary with regard to the cognitive instruments used and domains assessed. The MoCA is a relatively brief cognitive screening instrument, and may not be sensitive to detect possible subtle cognitive advantages in language and executive functioning, which may be more reliably associated with bilingual advantages when these relationships are observed 25 …”
Section: Discussionmentioning
confidence: 99%